Students' Critical and Creative Thinking Ability Based on Digital Literacy: Case Study of Accounting Students in Bogor - Warizal, Warizal; Roestamy, Martin; Hambani, Susy; Asri Humaira, Megan (Journal of World Science, 2023)
Digital literacy is an important issue today, especially for students. In the work environment, students are required to be fluent in technology, which is the basis of digital literacy skills. The research aims to find out and describe patterns of students' critical thinking and creative thinking abilities in the digital literacy-based Accounting department. The research uses a case study approach through a questionnaire, Google Forms, and semi-structured interviews. The data analysis technique uses thematic analysis techniques. The research results show that there are several components in the form of literature and benefits in digital literacy, as well as activities that demonstrate students' critical thinking and creative thinking skills based on their digital literacy. This research concludes that there are patterns that show that critical thinking skills and creative thinking skills are included in the 8 (eight) components of digital literacy, so these patterns are the novelty in this research. These patterns show a cause-and-effect relationship from having digital literacy skills.